Combustion Dynamics of an Extreme Fuel-Rich Throttleable Rocket Engine During Continuously Throttling Process. Issue 4 (3rd April 2017) - Cheng, Peng; Li, Qinglian; Kang, Zhongtao; Zhang, Xinqiao
ABSTRACT: An experimental study has been conducted to investigate the dynamics of an extreme fuel-rich throttleable rocket engine during continuously throttling process. The rocket engine burned kerosene (RP-1) and oxygen and it was continuously throttled in fire tests by adjusting the flow rate of kerosene. Dynamic response of chamber pressure was analyzed. Results show two phenomena named hysteresis of characteristic velocity and anti-regulation of chamber pressure during the throttling process. When characteristic velocity hysteresis occurs, transient characteristic velocity is higher in condition of increasing mixture ratio (MR) and lower in condition of decreasing MR than steady value during throttling process. The anti-regulation can be induced by throttling or purging process. In addition, both throttling method and throttling rate influence the amplitude and duration of anti-regulation. Finally, the response of chamber pressure to the throttling was divided into two periods, namely ramp response and step response. From the step response, the combustion system is characterize as a first order system with a time constant T = 133 ms.